Estimating the Cost of Housing in the Irish Market: A Rental Equivalence Approach - Allen-Coughlan, Matthew; Coffey, Cathal; Martinez-Cillero, Maria; Kostarakos, Ilias; McQuinn, Kieran; O'Toole, Conor (The Economic and Social Review, 2022)
Measuring the cost of housing for official estimates of inflation is of particular importance given the share of household expenditure that housing accounts for. In this paper, we present a measure of owner-occupier housing inflation using a rental equivalence approach for Ireland. We use supervisory microdata on tenancy registrations from the Residential Tenancies Board coupled with census data on owner occupation by region and housing type to develop an estimate of rental equivalence for the period 2015 to 2019. We then use this housing cost in an estimate of inflation and find that adopting such a measure would increase the headline Consumer Price Index (CPI) by 1.6 percentage points in September 2019. We also discuss data and measurement issues with our approach, compare our index to other publicly available data and suggest areas for future research.